ANALISIS KEBUTUHAN INFORMASI AKUNTANSI PADA UKM DI KOTA PADANG - Putri, Amanda; Adelia, Fina; Akbar, Farras Atha; F. D., Gezah Berkah Akbar; Widiastuty, Erna; Febrianto, Rahmat (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2023)
Accounting information is an important medium in business operational activities. Accounting information help owners in making business decisions. This community service aims to analyze the accounting information needs of Small and Medium Enterprises (UKM) in the city of Padang. The method used in this activity was observation and interviews with SME owners in Padang City. As a result, business owners need information about the inventory of their merchandise. Inventory information is needed because it relates to information on the amount of capital spent to purchase merchandise inventory. Thus, information regarding recording the amount of inventory via an inventory card is expected to help the owner to find out accounting information related to the correct amount of inventory.